PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN PADA PRODUK WARDAH DI KOTA PEKANBARU - , Deni Danar Rahayu, Widya Laila Pertiwi , Aida Nursanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This research was Wardah Brand Beauty Products in Pekanbaru City. With the aim to know and analyze the influence of Product Quality And Brand Image To Custumer Satisfaction And Custumer Loyalty On Beauty Products Wardah Brand In Pekanbaru City. The sample used in this research is 120 custumer with criteria 17 years and over.  The analytical tool used in this research is Path Analysis with SPSS version 23. The results show that: 1) Product Quality Has a Positive and Significant Influence on Customer Satisfaction, 2) Brand Image Has a Positive and Significant Influence on Customer Satisfaction, 3) Product Quality Has a Positive and Significant Influence on Customer Satisfaction, 3) Product Quality Has a Positive and Significant Influence on Customer Satisfaction  Significant to Customer Loyalty, 4) Brand Image Has a Positive and Significant Influence on Customer Loyalty, 5) Product Quality Has a Positive and Significant Influence on Customer Loyalty Through Customer Satisfaction, 6) Brand Image Has a Positive and Significant Influence on Product Loyalty Through Customer Satisfaction, 7) Satisfaction  Customers Have a Positive and Significant Influence on Customer Loyalty. Keywords: Product Quality, Brand Image, Custumer Satisfaction, Custumer Loyalty.